Building systems for interior designers - Binggeli, Corky (Hoboken, N.J. : John Wiley & Sons, 2010)
Addresses the special concerns of the interior designer within the context of the rest of the building design team. This book explains technical building systems and engineering issues. Covering systems from HVAC to water and waste to lighting, transportation, and safety, it helps interior designers to communicate more effectively with architects.
boek